Comparison of static hysteresis models subject to arbitrary magnetization waveforms - Petrun, Martin; Steentjes, Simon; Hameyer, Kay; Dolinar, Drago (Compel, 2017)
Purpose This paper aims to compare different static history-independent hysteresis models (mathematical-, behavioural- and physical-based ones) and a history-dependent hysteresis model in terms of parameter identification effort and accuracy. Design/methodology/approach The discussed models were tested for distorted-excitation waveforms to explore their predictions of complex magnetization curves. Static hysteresis models were evaluated by comparing the calculated and measured major and minor static hysteresis loops. Findings The analysis shows that the resulting accuracy of the different hysteresis models is strongly dependent on the excitation waveform, i.e. smooth excitations, distorted flux waveforms, transients or steady-state regimes. Obtained results show significant differences between predictions of discussed static hysteresis models. Research limitations/implications The general aim was to identify the models on a very basic and limited set of measured data, i.e. if possible using only the measured major static loop of the material. The quasi-static major hysteresis loop was measured at Bmax = 1.5 T. Practical/implications The presented analysis allows selection of the most-suited hysteresis model for the sought-for application and appraisal of the individual limitations. Originality/value The presented analysis shows differences in intrinsic mechanisms to predict magnetization curves of the majority of the well-known static hysteresis models. The results are essential when selecting the most-suited hysteresis model for a specific application.